Balancing Social and Regional Equity: Higher Education Policy Trajectory in Kerala. (July 2019) - Mathew, A.
Kerala State higher education policy is a narrative of the government's perpetual engagement to safeguard its regional and social equity, evolved consciously since its erstwhile princely rule. With more than three-fourths of colleges under private managements, only Kerala, in India, manages to keep at bay the pressure by the unaided private managements for a free run in education and higher education, which, with its relatively inexorable propensity to privatization and commercialization, significantly damages its equity. The Kerala State Higher Education Council, established in 2007, has been a touchstone of this policy ethos to unremittingly sustain equity, access, and excellence through state control.